EARLY CHILDHOOD BILINGUALISM AS A DRIVER FOR SOCIAL INCLUSION AND EQUALITY - Sultanova Shohistaxon Shavkatovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Annotation: This paper explores how early childhood bilingualism can serve as a powerful catalyst for promoting social inclusion and equality in multicultural and multilingual societies. Drawing on empirical research, the study highlights the cognitive, academic, and socio-emotional benefits of acquiring two languages during early developmental stages. It further examines how bilingualism can bridge social divides, reduce educational inequalities, and enhance participation in civic life. The discussion includes case studies from both developed and developing countries, demonstrating that early bilingual education fosters mutual respect, intercultural understanding, and equitable opportunities for children from diverse linguistic backgrounds.